Digital gene atlas of neonate common marmoset brain. (March 2018) - Shimogori, Tomomi; Abe, Ayumi; Go, Yasuhiro; Hashikawa, Tsutomu; Kishi, Noriyuki; Kikuchi, Satomi S.; Kita, Yoshiaki; Niimi, Kimie; Nishibe, Hirozumi; Okuno, Misako; Saga, Kanako; Sakurai, Miyano; et al.
Highlights: World first web accessible common marmoset brain ISH expression atlas database. User friendly system to search gene expression in marmoset brain. High throughput gene expression analysis for cross species comparative analysis. Abstract: Interest in the common marmoset ( Callithrix jacchus ) as a primate model animal has grown recently, in part due to the successful demonstration of transgenic marmosets. However, there is some debate as to the suitability of marmosets, compared to more widely used animal models, such as the macaque monkey and mouse. Especially, the usage of marmoset for animal models of human cognition and mental disorders, is still yet to be fully explored. To examine the prospects of the marmoset model for neuroscience research, the Marmoset Gene Atlas (https://gene-atlas.bminds.brain.riken.jp/ ) provides a whole brain gene expression atlas in the common marmoset. We employ in situ hybridization (ISH) to systematically analyze gene expression in neonate marmoset brains, which allows us to compare expression with other model animals such as mouse. We anticipate that these data will provide sufficient information to develop tools that enable us to reveal marmoset brain structure, function, cellular and molecular organization for primate brain research.